2015
DOI: 10.1108/tqm-01-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Success factors and organizational approaches for the implementation of energy management systems according to ISO 50001

Abstract: Purpose – The purpose of this paper is to identify main success factors for the effective implementation, operation and certification of an energy management system (EnMS) in accordance with ISO 50001, which represents the fastest growing standard for management systems in the world (International Organization for Standardization, 2013). Design/methodology/approach – Due to rising energy costs, increasing global competitive pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 2 publications
(3 reference statements)
0
25
2
1
Order By: Relevance
“…These good results are also an additional motivation for competitors to implement the standard. Karcher and Jochem [11] also found that the positive results of ISO 50001, in terms of monetary savings, motivate other organizations to implement it. Moreover, they also state that the main enabler is the positive attitude of the staff.…”
Section: Description Of the Iso 50001 Standard And Literature Reviewmentioning
confidence: 97%
“…These good results are also an additional motivation for competitors to implement the standard. Karcher and Jochem [11] also found that the positive results of ISO 50001, in terms of monetary savings, motivate other organizations to implement it. Moreover, they also state that the main enabler is the positive attitude of the staff.…”
Section: Description Of the Iso 50001 Standard And Literature Reviewmentioning
confidence: 97%
“…ISO 9001 is a process essentially designed to establish what the customer desires, and then satisfy those desires [23,39,28].…”
Section: Qms Contribution To the Establishment Of World-class Processmentioning
confidence: 99%
“…Management systems should not be viewed in isolation, because their structures are interlinked. Management standards overlap each other, and might form bases for each other [24,28].…”
Section: The Effect Of a Qms On Establishing A Sustainable Long-term mentioning
confidence: 99%
“…support the creation of public and private policy programmes to mitigate the identified barriers (cost and technical expertise tend to be critical barriers); evaluating the results and benefits of the integration of ISO 14001 and 50001 in the context of supply; verifying empirically how the Table 2 would collaborate to develop a green supply chain more efficient in terms of energy and low carbon; analysing organisational resources, which should be developed to integrate ISO 50001 and GSCM, such as green training (Jabbour and de Sousa Jabbour 2014) and teamwork based on specific technical expertise (Karcher and Jochem 2015); exploring perception of managers with regard to how the integration between ISO 50001 and GSCM contribute to a sustainable competitive advantage in a context of environmental constraints (climate change) (Hart 1995); and discussing how low-carbon supply chains enable firms to respond to the challenges and demands posed by the natural environment (Chan et al 2015). Some limitations of this research can be point out.…”
Section: Reverse Logistics Energy Review Designmentioning
confidence: 99%